Control of Aspergillus flavus Growth in Tomato Paste by Cinnamomum zeylanicum and Origanum vulgare L. Essential Oils - Kalantary, F (Fakultas Farmasi, Universitas Gadjah Mada, 2014)
This study was conducted to evaluate the antifungal activities of cinnamon (Cinnamomum zeylanicum) and oregano (Origanum vulgare L.) essential oils against Aspergillus flavus in culture media and tomato paste. The chemical compositions of the essential oils were determined by Gas Chromatography-Mass Spectroscopy (GC-MS). Trans- cinnamaldehyde was found to be the main constituent of Cinnamomum zeylanicum essential oil (CZEO), followed by methyl eugenol, Î´- cadinene and Î³- cadinene. The major components of Origanum vulgare L. essential oil (OVEO) were limonene, caryophyllene oxide, Î±-ionone, germacreneâ€“ D, Î³- terpinene, Î²- pinene and terpinene-4-ol. For evaluating antifungal activities of CZEO and OVEO,Â A. flavus PTCC: 5006, was inoculated in Sabouraud Dextrose Broth (SDB) and tomato paste, then 0, 50, 100, 200, 300, 400, 500 and 600 ppm of essential oils were added to each sample and incubated at 25Â±0.5oC for 30 and 60 days, respectively. The antifungal activity was measured by Agar Dilution method. The EOs at all tested concentrations had inhibitory effect against A. flavus growth. 200 ppm of CZEO and 500 ppm of OVEO completely inhibited A. flavus growth in culture media, while in tomato paste 300 ppm of CZEO and 200 ppm of OVEO had the same effect. Test panel evaluations were carried out in tomato ketchup base and samples with 100 and 200 ppm CZEO were accepted by panelists. The results may suggest the potential replacement of antifungal chemicals by CZEO as natural inhibitor to control A. flavus growth in tomato paste.